The manifestations of the scientific renaissance in the Tihama of Yemen and its impact on the shariah sciences مظاهر النهضة العلمية يف هتامة اليمن وأثرها يف العلوم الشرعية - Mohamed Fathy, Mohamed Abdelgelil; Kamarudin, Awang Mat (2020)
The research problem emerges in the knowledge of the scientific life in the Tihama region of Yemen and its impact on the development of Shariah sciences in it, as it did not get its luck enough of research and care as much as other Islamic cities, where this study aims to know the manifestations of the activity of the scientific movement in it, and how encourage and contribute effectively to creativity and authorship in various sciences and knowledge, and the method used is: the inductive approach, and the descriptive approach with analysis of the manifestations of scientific activity and knowledge of the causes of stagnation in authorship and creativity. And in the end; the researcher concluded that there is a scientific movement rich in rare works that Islamic law students need in various fields in the sciences of the Qur'an, interpretation (Tafsir), jurisprudence (Fiqh), Hadith and others.